Differences between renal effects of venom from two Bothrops jararaca populations from southeastern and southern Brazil. (January 2017) - Jorge, Roberta Jeane Bezerra; Jorge, Antônio Rafael Coelho; de Menezes, Ramon Róseo Paula Pessoa Bezerra; Mello, Clarissa Perdigão; Lima, Danya Bandeira; Silveira, João Alison de Moraes; Alves, Natacha Teresa Queiroz; Marinho, Aline Diogo; Ximenes, Rafael Matos; Corrêa-Netto, Carlos; Gonçalves Machado, Larissa; Zingali, Russolina Benedeta; et al.
Abstract: Components from animal venoms may vary according to the snake's age, gender and region of origin. Recently, we performed a proteomic analysis of Bothrops jararaca venom from southern ( BjSv ) and southeastern ( BjSEv ) Brazil, showing differences in the venom composition, as well as its biological activity. To continue the study, we report in this short communication the different effects induced by the BjSEv and BjSv on isolated kidney and MDCK renal cells. BjSEv decreased perfusion pressure (PP) and renal vascular resistance (RVR) and increased urinary flow (UF) and glomerular filtration rate (GFR), while BjSv did not alter PP and RVR and reduced UF and GFR. Both types of venom, more expressively BjSEv, reduced %TNa +, %TK + and %Cl − . In MDCK cells, the two types of venom showed cytotoxicity with IC50 of 1.22 μg/mL for BjSv and 1.18 μg/mL for BjSEv and caused different profiles of cell death, with BjSv being more necrotic. In conclusion, we suggest that BjSv is more nephrotoxic than BjSEv . Highlights: Bothrops jararaca venoms from south and southeast Brazil have different renal effects. B. jararaca venom ( Bjv ) from south is more nephrotoxic than from Bjv from southeast. Bjv from south showed characteristics of renal injury on isolated kidney. Bjv from southeast showed a diuretic effect on isolated kidney. Bjv from south showed a higher necrotic profile than Bjv from southeast in MDCK cells.